Feasibility of Material in Motion Comic: Proclamation of Independence in the Perspective of Multicultural Values - Taat Wulandari (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research and development aims to: 1) investigate the social studies learning media of motion comic on multicultural values in the materials of independence proclamation. This research and development utilized the Borg Gall model. The stages of development were: 1) gathering information; 2) planning; 3) developing product; 4) validating. The results of this study indicate that all aspects of the assessment obtain good results. According to learning media material experts, Motion Comic gets a percentage of 98% and is in the very good category, which is very feasible to use. The multicultural values contained in the motion comics include tolerance, respect and appreciation, learning to live in differences, conflict resolution, mutual trust and maintaining mutual understanding and respect.